The Effect of Aerobic Exercise on TNF-Alpha in older adults - Santosa, Donabella Fortuna; Wahyuni, Nila (Sport and Fitness Journal, 2024)
Inflamation and muscle mass and function is the problem the aging process. This literature review evaluate the aerobic exercise efficacy on TNF-? in older adults. This literature review will investigate the effect of aerobic exercise determined by TNF-? level analysis in the older adult patient. Google Scholar, ResearchGate, and Mendeley were used as the search engine. The keywords were aerobic exercise, TNF-? & older adults to analyze seven articles. A significant effect on inflammatory marker proofed by TNF-? improvement. The change TNF-? level was various, but another clinical progress such as cardiovascular, endocrine, and other research parameter. Aerobic exercise can be an alternative way to maintain inflammatory process in older adult patients.